INTERACTIVE CONSTRUCTION AND CORRECTION OFRATIONAL SCHEMES FOR CUTTING NATURAL MATERIALS WITH COMPLEX CONFIGURATION OF EXTERNAL CONTOURS ON DETAILS OF HABERDARD PRODUCTS - CHUPRYNKA, VIKTOR; NAUMENKO, BOGDAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper considers one of the important tasks of automated design of rational schemes for cutting natural materials with a complex shape of the external contour on details of leather goods, namely the task of interactive construction and correction of rational schemes for cutting natural materials with a complex shape of the external contour on details of leather goods, designed in automatic mode.To successfully solve this problem, a technological and mathematical formulation of this problem is given.In the problem of interactive construction and correction of rational cutting schemes designed in automatic mode for natural materials with a complex shape of the external contour, the main structural components for the mathematical model were selected and an analytical description of each of these components was presented.Using the analytical description of the selected structural components, algorithms for implementing this problem were proposed in a software product for interactive construction and correction of rational cutting schemes designed in automatic mode for natural materials with a complex shape of the external contour for leather goods parts.The developed software product provides:- input of information about the zonal contours of the natural material, defects in the material and parts of the model for which a rational cutting scheme is designed in an interactive mode;- interactive removal of any part from the cutting scheme:- interactive addition of an active part to the required place on the material. This ensures control over the non-intersection of the active part with the material contour, defects on the material and other parts already placed in the cutting scheme;- determination of the percentage of material use in the designed cutting scheme;- saving the necessary information in the file about the designed cutting scheme;- printing the designed cutting scheme.The developed software product has a friendly interface and does not require additional knowledge of computer science when working with it. This product can be useful in preparatory and cutting production in the light industry.
Keywords: cutting scheme; haberdashery; algorithm; software product; interactive adjustment; method of angles; material defects; natural material